2021
DOI: 10.1016/j.jtumed.2020.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Determining the correlation between Cobb angle severity and bone mineral density in women with adolescent idiopathic scoliosis

Abstract: Objectives To determine the correlation between Cobb angle severity and varying bone mineral density (BMD) and measure the prevalence of low BMD in women with adolescent idiopathic scoliosis (AIS) in KSA. Methods The sample included 54 women with AIS between 10 and 20 years of age. Data regarding Cobb angles and femoral and lumbar Z-scores according to dual-energy X-ray absorptiometry (DXA) scans performed between 2008 and 2018 were reviewed. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
4
7
0
1
Order By: Relevance
“…We found that piezo1 11aa del/11aa del at 3 months of age had predominantly lower TMD values than the wildtype (Figure 3C). This is consistent with various reports when they assessed the bone mineral density in scoliotic patients (Sarioglu et al, 2019;Li et al, 2020;Almomen et al, 2021).…”
Section: Resultssupporting
confidence: 93%
“…We found that piezo1 11aa del/11aa del at 3 months of age had predominantly lower TMD values than the wildtype (Figure 3C). This is consistent with various reports when they assessed the bone mineral density in scoliotic patients (Sarioglu et al, 2019;Li et al, 2020;Almomen et al, 2021).…”
Section: Resultssupporting
confidence: 93%
“…However, A recent study of Almomen et al 24 reported a higher incidence of low bone mass (62.9% and 74.1% for lumbar and femoral BMD, respectively). This may be due to their study involved AIS patients with Cobb angles ≥ 40 o .…”
Section: Discussionmentioning
confidence: 92%
“…Li et al reported that AIS patients had poorer bone mineral density of the bilateral femoral neck than controls ( 13 ), and lower bone volume from the histological sections of the spinous process taken from AIS patients was found ( 33 ). Besides, Almomen et al reported that female AIS patients with greater higher Cobb angles exhibited a significantly higher risk of low bone density ( 34 ). Our study is the first to use the HU value obtained from CT scans to evaluate the bone quality of vertebral bodies in AIS patients.…”
Section: Discussionmentioning
confidence: 99%